Using the Photostress Method to Determine the Residual Stresses - Alzyod, Hussein; Ficzere, Peter (International Journal of Engineering and Management Sciences, 2022)
Strains and stresses in loaded and photoelastically coated structural members can be determined using the PhotoStress method. The quantitative values of variations in the principal strains (stresses) and their directions could be employed to get the strain or stress components field on the entire coated surface. In the PhotoStress experiment, isochromatic fringes give qualitative and quantitative information. It provides a source of information on the directions and magnitudes of principal strain and principal normal stress on the surface of photoelastic coated parts. This article reviews the principle of using PhotoStress analysis to measure the residual stress and provides the boundary condition of using this method.